2013
DOI: 10.1163/15685314-12341278
|View full text |Cite
|
Sign up to set email alerts
|

Views and Values on Family among Filipinos: An Empirical Exploration

Abstract: The Filipino family provides an interesting study because familism is embedded in its social sphere, translating its relational quality outside the family. Being family-centred, child-centric, having close ties, and a large family size (Medina, 2001; Miralao, 1994) are some basic elements of families in the Philippines. Applying regression on the data from the World Values Survey for the Philippines in 1996 and 2001, this study aims to explore the correlates of views on family values among Filipinos, specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Past evidence posited that parents experience greater meaning in life, satisfaction, and greater positive emotions explaining why parents tend to report less psychological distress (Nelson et al, 2014 ) compared to non-parent participants. Culturally, Filipinos place a high premium on family-centered values (Morillo, Capuno, & Mendoza, 2013 ). Despite the weight and pressure of responsibilities that Filipino parents shoulder (Aassve, Goisis, & Sironi, 2012 ), it appears that their children serve as a protective factor from severe mental health problems by serving as parents’ main sources of joy, inspiration, and meaning (Aassve et al, 2012 ; Nelson, Kushlev, English, Dunn, & Lyubomirsky, 2013 ) in the midst of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Past evidence posited that parents experience greater meaning in life, satisfaction, and greater positive emotions explaining why parents tend to report less psychological distress (Nelson et al, 2014 ) compared to non-parent participants. Culturally, Filipinos place a high premium on family-centered values (Morillo, Capuno, & Mendoza, 2013 ). Despite the weight and pressure of responsibilities that Filipino parents shoulder (Aassve, Goisis, & Sironi, 2012 ), it appears that their children serve as a protective factor from severe mental health problems by serving as parents’ main sources of joy, inspiration, and meaning (Aassve et al, 2012 ; Nelson, Kushlev, English, Dunn, & Lyubomirsky, 2013 ) in the midst of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the consistency of familial bonds as factors that promote the outcome, even when members did not share the same household, points to the importance of relatives as a supportive structure for those suspected of having TB. This is particularly relevant and specific to the context of the Philippines as close and strong family ties are at the core of Filipino culture ( Morillo et al, 2020 ). In a systematic review that examined the functions of social capital at the level of the family, the authors found the exertion of social influence and the exchange of social support to be key mechanisms through which family social capital can affect health ( Alvarez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also reasonable to bring the strong correlations between Filipino fathers and mothers' parental behaviors to the fore. A Filipino family is a child-centric social institution in which parents do what is best for their children (Morillo et al, 2013). In terms of their children's education, Filipino couples make mutual decisions given that their children's academic achievements are their source of pride and compensation for their sacrifices (Alampay, 2014).…”
Section: Discussionmentioning
confidence: 99%